Human development and its effect on Oman community in achieving sustainable development / Talib Ali Musabah Alsiyabi - Talib Ali, Musabah Alsiyabi (2017)
This study is about “human development and its effects to achieve sustainable development in Oman”. The aim of the study is to demonstrate the concepts, aims, areas, indicators and challenges of sustainable development. The study also aims to demonstrate the importance of human development and its influence to achieve sustainable development in Oman. Furthermore, the study aimed: 1- to demonstrate the government expenditure to develop health and education sectors, 2- to demonstrate the per capita income and the effect of human development to achieve the sustainable development in the Omani society. The study has been carried out by two main approaches/methods. The first approach was a rigorous review to the literature (previous studies). The second approach was a “case study” by which an experimental investigation took place. The experimental part is divided into two phases: 1- creating and developing a model showing and illustrating government expenditure first on the education and health sectors and second illustrating per capita income, according to the annual criteria of the United Nation, in developing human development in Oman, 2- a questionnaire has been used in the study to demonstrate the effect of human development to achieve sustainable development in Oman. The second phase of the case study included 356 participants belonging and working to the Supreme Council for Planning, the State Councils, the Main Municipality, Omani Company for Trade and Industry, Omani Women’s Association and another sample from health and education sectors. The study has proved the first hypothesis to be true, while the second and third hypotheses are proved true. This is due to the negative results that the study has demonstrated. The main hypothesis, however, has been proved true, shown a difference in the findings and perspectives of different researchers. According to the findings, the study recommends that government expenditure should be guided, well-supervised and reconsidered to effectively support education and health sectors. This may guarantee that government expenditure goes to the right people in charge in accordance with specific and fixed criteria that help increase and sustainability in the country’s incomes.